2017
DOI: 10.1158/1055-9965.epi-16-0889
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Number of Women Living with Metastatic Breast Cancer in the United States

Abstract: Background Distant metastatic breast cancer (MBC), including metastases found at diagnosis (de novo) and those occurring later (recurrence), represents the most severe form of the disease, when resource utilization is most intensive. Yet, the number of women living with MBC in the US is unknown. The objective of this paper is to use population-based data to estimate the prevalence of MBC. Methods We used a back-calculation method to estimate MBC prevalence from US BC mortality and survival from the Surveilla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
306
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 420 publications
(331 citation statements)
references
References 18 publications
2
306
2
2
Order By: Relevance
“…As of January 1, 2019, there were more than 3.8 million women with a history of breast cancer living in the United States. This estimate includes more than 150,000 women living with metastatic disease, three‐quarters of whom were originally diagnosed with stage I, II, or III breast cancer …”
Section: Selected Findingsmentioning
confidence: 99%
“…As of January 1, 2019, there were more than 3.8 million women with a history of breast cancer living in the United States. This estimate includes more than 150,000 women living with metastatic disease, three‐quarters of whom were originally diagnosed with stage I, II, or III breast cancer …”
Section: Selected Findingsmentioning
confidence: 99%
“…Survival rates for de novo MBC have increased substantially since the early 1990s [2], in part due to advances in medical treatment [3]. Therefore, the MBC population is growing, with 154,794 women estimated to be living with MBC [2]. Most research has focused on extending the lives of people with MBC, rather than maintaining or improving quality of life (QOL).…”
Section: Introductionmentioning
confidence: 99%
“…In these cases a primary treatment goal is symptom palliation (6,7). Patients with distant metastasis at initial diagnosis are classified as de novo stage IV metastatic patients and can be viewed as a distinct subgroup (8,9), and these patients could be considered a poor prognostic group with incurable disease. However, a previous report suggested that de novo BC patients tend to have a better prognosis relative to recurrent BC patients (10).…”
mentioning
confidence: 99%